2012
DOI: 10.1177/0959680111430656
|View full text |Cite
|
Sign up to set email alerts
|

Post-accession migration in construction and trade union responses in Denmark, Norway and the UK

Abstract: The article provides a comparative analysis of trade union responses to the arrival of CEE workers in Denmark, Norway and the UK, with a special emphasis on the organizing efforts of construction workers' unions. Organizing has been seen as a crucial element in avoiding a situation where the presence of CEE workers may lead to low-wage competition and social dumping. On the basis of case studies from Copenhagen, Oslo and the North-East of England the article analyses how the unions' strategies on recruiting mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 25 publications
(40 reference statements)
1
66
0
1
Order By: Relevance
“…In addition to research on firm recruitment practices, regulatory change and trade union enforcement (e.g. Fellini et al 2007;MacKenzie and Forde 2009;Cremers 2011;Wagner 2014;Eldring et al 2012), this chapter analysed worker practices and shows that it is workers' (strategic) behaviour that intentionally and unintentionally contributes to the continuation of current oppressive employment relations. As shown, manoeuvring the job market as it is currently organised creates strategic rewards for many of these…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition to research on firm recruitment practices, regulatory change and trade union enforcement (e.g. Fellini et al 2007;MacKenzie and Forde 2009;Cremers 2011;Wagner 2014;Eldring et al 2012), this chapter analysed worker practices and shows that it is workers' (strategic) behaviour that intentionally and unintentionally contributes to the continuation of current oppressive employment relations. As shown, manoeuvring the job market as it is currently organised creates strategic rewards for many of these…”
Section: Resultsmentioning
confidence: 99%
“…Union organising literature focuses on how changes in power relations at the workplace level can be achieved (Heery 2005;Bronfenbrenner 1998), whereas critical industrial relations literature links workplace struggles to inequalities cast by society at large (Elger 2001). Though some trade unions may have been reluctant in the past to represent migrant workers (Penninx and Roosblad 2000), studies have shown that immigrants, migrant workers with settling intentions and circular migrants do join trade unions when unions make strategic and resourceful efforts to include them (Pereira 2007;Skjaervø 2011;Eldring et al 2012;Milkman 2000). However, an increasing share of migrant workers, especially in construction, does not settle down in certain places but continues to move between contracts, worksites and countries.…”
Section: From Collective Agency To a Refined Understanding Of Worker mentioning
confidence: 99%
See 3 more Smart Citations